2018
DOI: 10.1108/ejm-10-2017-0760
|View full text |Cite
|
Sign up to set email alerts
|

Food literacy, healthy eating barriers and household diet

Abstract: PurposeFood literacy is an emerging concept associated with the skills, capabilities and knowledge to prepare a healthy diet and make healthy food choices. This study aims to examine how a dietary gatekeeper’s intentions to prepare a healthy diet for their family, and the subsequent satisfaction that a healthy diet is achieved, is influenced by their food literacy and by barriers to healthy eating.Design/methodology/approachA two-stage cross-sectional study was undertaken with 756 dietary gatekeepers who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 115 publications
3
80
0
1
Order By: Relevance
“…Secondary analysis of the US National Health and Nutrition Examination Survey showed that most women and men reported sharing meal planning, preparing and food shopping activities (meal planning and preparation: women 54% and men 56%, food shopping: women 60% and men 57%), but women had a higher likelihood of reporting having the main responsibility for meal planning and food shopping [41]. Research with well-educated dietary gatekeepers in Australia who were recruited through market research demonstrated the role of food literacy for overcoming barriers to healthy eating and positive intentions for healthy food preparation [56]. Efforts to improve food literacy in dietary gatekeepers will have positive effects on diet quality for other household members [57].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary analysis of the US National Health and Nutrition Examination Survey showed that most women and men reported sharing meal planning, preparing and food shopping activities (meal planning and preparation: women 54% and men 56%, food shopping: women 60% and men 57%), but women had a higher likelihood of reporting having the main responsibility for meal planning and food shopping [41]. Research with well-educated dietary gatekeepers in Australia who were recruited through market research demonstrated the role of food literacy for overcoming barriers to healthy eating and positive intentions for healthy food preparation [56]. Efforts to improve food literacy in dietary gatekeepers will have positive effects on diet quality for other household members [57].…”
Section: Discussionmentioning
confidence: 99%
“…To enhance diabetes awareness both in the general population and in at-risk groups (e.g. individuals with impaired glucose tolerance or those with low literacy), governments should employ communication strategies based on targeting, the use of multiple media channels [42] and the involvement of an individual's support network, such as family and friends, as well as physicians [92][93][94][95]. Government strategies aiming to decrease the prevalence of risk factors for GDM should employ a broad spectrum of media channels to increase awareness rather than relying solely on the effectiveness of prepregnancy care [50,51].…”
Section: Evidence-based Communication Strategiesmentioning
confidence: 99%
“…Despite being an increasingly recognised term, there is not yet a shared understanding of the construct's meaning and its components, resulting in a lack of theoretical consensus [8,9]. Most acknowledged empirical conceptualisations of food literacy include (i) the framework of Vidgen and Gallegos from Australia [3,7,10,[14][15][16][17][18][19][20], and (ii) the work of Desjardins and colleagues from Canada [21], which was later on revised by Thomas and coauthors [12,13,15]. Also from Canada, conceptualisations from (iii) Slater and coauthors [7,15,18] and from (iv) Cullen and colleagues [7,15,18,22,23] are considerably mentioned within the literature.…”
Section: Introductionmentioning
confidence: 99%